(untitled) (Research, Society and Development, 2021)
Digital Information and Communication Technologies are present in all sectors of society, including Education. Despite this, research has indicated the difficulty of teachers to integrate digital educational resources in their pedagogical practice. In this sense, this study presents a discussion about the pedagogical practice of teachers from a municipal public school in the city of Fortaleza in relation to the use of technology, before the pandemic. The research had a qualitative approach, with a descriptive and explanatory study. We analyzed the methodology used and the difficulties found to teach classes that use digital educational resources, through semi-structured interviews, questionnaires and classroom observations. The results point to the need for a rationalized planning in conjunction with teachers, as well as the need for continuing education for these professionals, with the participation of learning communities that favor the production of knowledge. Future research points to the need for pedagogical monitoring for a qualitative and quantitative overview of practices during and after the pandemic.